Truthfulness, Beneficence, and Vulnerability as Key Concepts in Communication Ethics - Aznar, Hugo (The ecumenical review, 2020)
This article presents the major stages of the approaches to the ethics of communication and the respective ethical principle of each one. The first stage, centred on the principle of truthfulness, was born at the beginning of the 20th century, at the same time as the first great development of the press and journalism. The second stage, which began at the end of the 20th century, centred on the principle of beneficence and developed from the growing influence of the mass media on all fields and aspects of social life. There is also the need for a further principle for communication ethics: the principle of vulnerability: to give voice to those affected by a situation, especially to those in a situation of vulnerability. The article then considers whether the huge impact of the Internet and social media at the beginning of the 21st century implies a new stage in the ethics of communication or rather the need to extend the scope and effectiveness of existing ethical principles and norms. The article tends toward the second option, insisting on the role of self-regulation and media literacy in tackling the current challenges in media and social media communications.